Motives that Matter: Conceptualizing a Theory of Needs, Knowledge Hiding, and Group Cohesion (TNKG) - Devi, Rajanala Ruchitha; Issac, Abraham Cyril (Journal of Knowledge Management Practice, 2026)
This study explores the influence of McClelland’s need for achievement, affiliation, and power on knowledge hiding and group cohesion in organizational settings. A qualitative research design consisting of open-ended essay questions with an inductive reasoning approach was used to conceptualize the theory of needs, knowledge hiding, and group cohesion (TNKG). The study reveals that motivational needs (affiliation, achievement, and power) influence knowledge hiding behaviour and group cohesion. Affiliation-oriented employees share knowledge, enhancing group cohesion, whereas achievement-oriented employees withhold knowledge to ensure a competitive edge, but not in all contexts. Power further influences knowledge hiding, with personalized power inducing strategic withholding and socialized power encouraging knowledge sharing for collective benefit. The study also reveals that knowledge hiding is not always dysfunctional, but a self-protective response to the perceived threat in the workplace. The study presents a theory of needs, knowledge hiding, and group cohesion. It offers new insights into the psychological motivations of knowledge-related behaviours in organizations, providing useful implications for enhancing knowledge management and team cohesion.
Keywords: knowledge management; needs; knowledge hiding; group cohesion; dependent personality; perceived organizational politics